Peramalan Volume Perdagangan Saham pada Bank X Menggunakan Extreme Learning Machine (ELM) - Rizki Arya Ramadhan; Marizsa Herlina (Bandung Conference Series: Statistics, 2024)
Abstract. The Indonesian stock market represented by the Indonesia Stock Exchange (IDX) has become an important part of national economic development. The IDX plays a very important role in supporting economic activities in Indonesia so that investors can reduce the risk of loss on the shares they own. Bank X is one of the largest private banking companies that plays a central role in the Indonesian capital market which has a capitalization value of $79.8 billion at the end of April 2023. Scientists, especially in the field of Artificial Intelligence (AI) are trying to develop and find methods in predicting stock price movements using technical analysis as science develops. Huang et al. (1) found a new learning method in Artificial Neural Networks, namely Extreme Learning Machine (ELM). ELM is a machine learning method developed for Artificial Neural Networks (JST). ELM focuses on artificial neural networks with a single hidden layer. The results of research on Extreme Learning Machine obtained the best hidden layer value of 60 with a MAPE value of 28.98% where the comparison of actual data and prediction data on Stock Trading Volume data at Bank X with Extreme Learning Machine method the data is not much different when using seed = 100 and random 1x. Abstrak. Pasar saham Indonesia yang diwakili oleh Bursa Efek Indonesia (BEI) telah menjadi bagian penting dalam pembangunan perekonomian nasional. BEI sangat berperan penting dalam mendukung kegiatan perekonomian di Indonesia sehingga investor dapat mengurangi risiko kerugian atas saham yang dimilikinya. Bank X merupakan salah satu perusahaan perbankan swasta terbesar yang berperan sentral di pasar modal Indonesia yang memiliki nilai kapitalisasi mencapai $79,8 miliar pada akhir April 2023. Para ilmuwan, khususnya di bidang Artificial Intelligence (AI) berusaha mengembangkan dan mencari metode dalam memprediksi pergerakan harga saham menggunakan analisis teknikal seiring berkembangnya ilmu pengetahuan. Huang et al. (1) menemukan metode pembelajaran yang baru pada Jaringan Syaraf Tiruan yaitu Extreme Learning Machine (ELM). ELM merupakan sebuah metode pembelajaran machine yang dikembangkan untuk Jaringan Syaraf Tiruan (JST). ELM berfokus pada jaringan syaraf tiruan dengan satu lapisan tersembunyi (single hidden layer). Hasil penelitian pada Extreme Learning Machine diperoleh nilai hidden layer terbaik yaitu 60 dengan nilai MAPE sebesar 28,98% dimana perbandingan data aktual dan data prediksi pada data Volume Perdagangan Saham pada Bank X dengan metode Extreme Learning Machine datanya tidak jauh berbeda ketika menggunakan seed = 100 dan acak 1x.